2019
DOI: 10.7240/jeps.450383
|View full text |Cite
|
Sign up to set email alerts
|

Ti6Al4V Surface Modification by Hydroxyapatite Powder Mixed Electrical Discharge Machining for Medical Applications

Abstract: Titanium surface modification by the Hydroxyapatite (HA) mixed Electrical Discharge Machining (EDM) is an alternative and promising technique to enhance the biocompatibility and to promote the biological performance in bone, which is dependent on surface properties, such as surface roughness, chemistry, and wettability. HA powder is used for the first time with electrical discharge machining to improve osteoblastic cell activity on the developed surfaces for Ti6Al4V. Different HA concentrations in deionized wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…For instance, with variation in the powder characteristics (particle sizes and concentrations) of SiC and Al 2 O 3 powders and dielectric mediums (such as EDM oil, deionized water, and tap water), considerable changes in the surface roughness (SR), recast layer thickness (RLT), material subtraction/removal rate (MRR), and tool wear rate (TWR) were witnessed [ 225 227 ]. Besides, the literature also records a noteworthy improvement in the biological response of PM-EDMed Ti alloys when the enhanced biocompatibility, osteoblastic cell activity, and bone-bonding ability were achieved using hydroxyapatite (HA) [ 228 230 ]. Two recent articles used silver nanopowder and obtained remarkable improvement in the antibacterial properties of PM-EDMed Ti-6Al-4 V alloy [ 215 , 231 ].…”
Section: Surface Modification Of Metallic Implant Biomaterialsmentioning
confidence: 99%
“…For instance, with variation in the powder characteristics (particle sizes and concentrations) of SiC and Al 2 O 3 powders and dielectric mediums (such as EDM oil, deionized water, and tap water), considerable changes in the surface roughness (SR), recast layer thickness (RLT), material subtraction/removal rate (MRR), and tool wear rate (TWR) were witnessed [ 225 227 ]. Besides, the literature also records a noteworthy improvement in the biological response of PM-EDMed Ti alloys when the enhanced biocompatibility, osteoblastic cell activity, and bone-bonding ability were achieved using hydroxyapatite (HA) [ 228 230 ]. Two recent articles used silver nanopowder and obtained remarkable improvement in the antibacterial properties of PM-EDMed Ti-6Al-4 V alloy [ 215 , 231 ].…”
Section: Surface Modification Of Metallic Implant Biomaterialsmentioning
confidence: 99%
“…To carry out the experimentation, ZNC EDM (S645, OSCARMAX, Taiwan) with a specially fabricated tank was employed and a pump for uniform mixing of powder was used as part of the setup (Figure 1). The experiments were conducted based on the Taguchi design with a five-factor mixed level setup and orthogonal array of L 16 (2) 15 . The experimental variables and their levels are shown in Table 2.…”
Section: N-hap Powder-mixed Edmmentioning
confidence: 99%
“…It has been recently indicated that it is possible to deposit HAp powder on the surfaces of different types of Ti alloys. [16][17][18][19][20] However, machining parameters of PMEDM can influence the properties of the final product (e.g. surface roughness (SR)) and the productivity of machining process (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent progress of surface modifications on hard tissue applications apart from surface coating strategy are introduced in Table S2. [ 167–181 ] It is suggested that physicochemical cues of the surface are intrinsically linked as the alteration of the surface topography will lead to localized changes in surface chemistry, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…We first focused on plasma sprayed CaP coatings on metallic implants and possible techniques to address their limitations including phase S2. [167][168][169][170][171][172][173][174][175][176][177][178][179][180][181] It is suggested that physicochemical cues of the surface are intrinsically linked as the alteration of the surface topography will lead to localized changes in surface chemistry, and vice versa.…”
Section: Introductionmentioning
confidence: 99%